Dialogues in Early South Asian Religions: Hindu, Buddhist and Jain Traditions. Edited by Brian Black and Laurie Patton. - Muldoon-Hules, Karen (Buddhist Studies Review, 2017)
Dialogues in Early South Asian Religions: Hindu, Buddhist and Jain Traditions. Edited by Brian Black and Laurie Patton. Routledge 2015, 2016. 265pp. Hb. £73.99, ISBN 13: 9781409440123. Pb. £22.99 (ISBN 13: 9781409440130). E-book £21.84, ISBN: 9781315576978.